Computational Identification of Antigenic Proteins and Epitopes in Hantavirus sp. for Drug Repurposing - Vartika Sahay (International Journal of Molecular Biotechnological Research, 2025)
Hantavirus is an emerging virus that spreads from animals to humans and can cause serious illnesses like hantavirus pulmonary syndrome (HPS) and hemorrhagic fever with renal syndrome (HFRS). there are no FDA-approved treatments available for these diseases. This study explores in-silico drug repurposing as a strategy to identify potential therapeutic candidates. The physicochemical, secondary structure, antigenicity, and post-translational modification analysis of hantavirus proteins – specifically the glycoprotein precursor, N protein, and non-structural (NS) protein – reveals promising targets for drug intervention. The results reveal that all proteins exhibit antigenic properties, with the NS protein showing the highest antigenicity due to its role as an interferon antagonist, making it a promising target for immune-modulating therapies. PTM analysis highlights extensive phosphorylation and glycosylation, particularly in the glycoprotein precursor and RdRp, suggesting potential intervention points through kinase inhibitors or glycosylation inhibitors to disrupt viral replication and immune evasion mechanisms. The secondary structure analysis identifies significant flexibility in the glycoprotein precursor, which could be used to design drugs that target its structural transitions critical for viral entry and assembly. The findings of this study provide valuable insights that can aid in the identification of appropriate drug for the treatment of Hantavirus infections. This study underscores the utility of computational methodologies in accelerating drug repurposing for emerging viral threats.
Keywords: Hantavirus; antigenicity; drug repurposing; in-silico; post-translational modifications; protein analysis